Modular fluorescence complementation sensors for live cell detection of epigenetic signals at endogenous genomic sites - Cristiana Lungu (Nature Portfolio, 2017)
Tools for imaging epigenetic modifications can shed light on the regulation of epigenetic processes. Here, the authors present a fluorescence complementation approach for detection of DNA and histone methylation at endogenous genomic sites allowing following of dynamic changes of these marks by live-cell microscopy.